Enhancing Civics Learning Outcomes Through Android Application-Based Media in Class VII C At SMP Shalahuddin Malang - Moh. Nurron Kholifatul Ardhi; Wahyu Rochmadi, Nur; Sukriono, Didik (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
This research departs from the problem of learning outcomes of students in class VII C SMP Shalahuddin Malang in Civics subjects that have not been completed classically 85%. To improve learning outcomes, use media in the teaching and learning process. The purpose of this study was to improve student learning outcomes by using android application-based media during learning. This research uses Classroom Action Research (CAR) which refers to the Kemmis and Mc Taggart model through several stages, namely: 1) planning stage, 2) action, 3) observation, and 4) reflection. The research location is at SMP Salahuddin Malang with the subject of class VII C which amounted to 22 students. Data collection techniques using observation, tests and documentation. The analysis used was qualitative analysis and simple quantitative analysis. The results showed that learning by using media based on android applications can improve the learning outcomes of students in class VII C SMP Shalahuddin Malang. The implications of these findings suggest that Implementing technology in education can be an effective solution to address the issue of low learning outcomes.